Temperature dependence of viscosity, relaxation times (T(1), T(2)) and simulated contrast for potential perfusates in post-mortem MR angiography (PMMRA) - Webb, Bridgette (Int J Legal Med, 2016)
Developments in post-mortem imaging increasingly focus on addressing recognised diagnostic weaknesses, especially with regard to suspected natural deaths. Post-mortem MR angiography (PMMRA) may offer additional diagnostic information to help address such weaknesses, specifically in the context of sudden cardiac death. Complete filling of the coronary arteries and acceptable contrast with surrounding tissue are essential for a successful approach to PMMRA. In this work, the suitability of different liquids for inclusion in a targeted PMMRA protocol was evaluated. Factors influencing cooling of paraffinum liquidum + Angiofil® (6 %) in cadavers during routine multiphase post-mortem CT angiography were investigated. The temperature dependence of dynamic viscosity (8–20 °C), longitudinal (T(1)) and transverse (T(2)) relaxation (1–23 °C) of the proposed liquids was quadratically modelled. The relaxation behaviour of these liquids and MR scan parameters were further investigated by simulation of a radiofrequency (RF)-spoiled gradient echo (GRE) sequence to estimate potentially achievable contrast between liquids and post-mortem tissue at different temperatures across a forensically relevant temperature range. Analysis of the established models and simulations indicated that based on dynamic viscosity (27–33 mPa · s), short T(1) relaxation times (155–207 ms) and a minimal temperature dependence over the investigated range of these parameters, paraffin oil and a solution of paraffin oil + Angiofil® (6 %) would be most suitable for post-mortem reperfusion and examination in MRI. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00414-016-1482-5) contains supplementary material, which is available to authorized users.